Parâmetros plasmáticos e digestibilidade aparente em equinos recebendo concentrado com óleo de arroz - Garcia, Helio Alberto Cuman (2011)
The experiment was conducted to evaluate the adding effect of rice oil in concentrates for horses through the test of apparent digestibility and blood parameters (glucose, cholesterol, triglycerides and high density lipopoliproteinas - HDL). There were used 12 horses six males and six females, mean age 18 ± 4 months and live weight of 306 ± 22.6 kg. The experimental design was a split plot in time repeated. The experiment lasted 90 days. The treatments consisted of increasing levels of rice bran oil in the concentrate of 0.0, 3.5, 7.0, 10.5, 14.0 and 17.5%, using daily intake of 2.25% BW, based on dry matter. The animals were housed in individual bay and diet divided into three meals. The first blood sample was performed in the 66 th day of the experiment and the other ones were performed every 12 days between them. For the measurement of serum glucose, cholesterol, triglycerides and HDL blood was collected by the left jugular venipuncture. To determine the total apparent digestibility of nutrientes it was performed total collect of feces. There was no effect (P>0.05) of diets on the apparent digestibility of dry matter, crude protein, ether extract, neutral detergent fiber and acid detergent fiber. Effect was observed (P<0.05) between diets on the apparent digestibility of gross energy (y= 64.55 ? 0.58x). There was no effect (P>0.05) of diets on serum glucose, but for the cholesterol parameter effect was found (P<0.01) an interaction of treat treatment x sex, being significant for females represented by (y= 73.92 + 2.08x). As for males, there was no effect (P>0.05). Considering the parameter triglyceride there was no effect (P<0.01) of diets (y= 15.73 ? 0.96x + 0.0524x2). Effect was observed (P<0.01) on serum HDL parameter (y= 45.24 + 1.0499x). It is concluded that the addition of rice bran oil was not harmful for nutrient digestibility, with exception to the gross energy. Only for females the supply of oil increased cholesterol levels, while this also influenced the serum levels of triglycerides and HDL for both sexes. The rice bran oil can be used in concentrate for growing horses.